2016
DOI: 10.20960/nh.342
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de lácteos durante la infancia y la adolescencia, ¿protege del riesgo cardiometabólico?

Abstract: Introduction: The high prevalence of obesity in children and adolescents is considered as a major global health concern and involves the onset of other comorbidities such as hypertension, dyslipidemia, chronic infl ammation and hyperinsulinemia, which are also considered as cardiovascular diseases risk factors. Several studies have observed that consumption of dairy products has a protective role on the development of cardiovascular diseases; however, the scientifi c evidence on this topic is very limited amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…But it is important to highlight that ERICA is the largest study with a representative sample of Brazilian There are few studies analysing the association between dairy products and T2DM in adolescents. The HELENA study (with a sample of adolescents aged between 12•5 and 17•5 years, from eight European cities) found that dairy products are the food group that best identifies adolescents with lower cardiovascular risk (62) . In Brazil, the latest surveys of Brazilian family budgets point to a decrease in the consumption of dairy products and their replacement with sweetened beverages in the general (63) .…”
Section: Discussionmentioning
confidence: 99%
“…But it is important to highlight that ERICA is the largest study with a representative sample of Brazilian There are few studies analysing the association between dairy products and T2DM in adolescents. The HELENA study (with a sample of adolescents aged between 12•5 and 17•5 years, from eight European cities) found that dairy products are the food group that best identifies adolescents with lower cardiovascular risk (62) . In Brazil, the latest surveys of Brazilian family budgets point to a decrease in the consumption of dairy products and their replacement with sweetened beverages in the general (63) .…”
Section: Discussionmentioning
confidence: 99%
“…In our proposal, seven positive components (fruits, vegetables, pulses, cereals, fish and seafood, monounsaturated/saturated fats ratio, and dairy products) and two negative components (meat and alcohol) were included. Since ethanol consumption is not recommended for children and adolescents, alcohol intake was scored as a detrimental component; and intake of dairy products was also scored as a beneficial component because dairy products are recommended in growing age [22,23]. We used age-and sex-specific median intakes of the study participants as a cut-off value for each component.…”
Section: Dietary Assessmentmentioning
confidence: 99%